Nursing Home Implementation of Health Information Technology: Review of the Literature Finds Inadequate Investment in Preparation, Infrastructure, and Training - Michelle Ko MD, PhD; Laura Wagner RN, PhD, FAAN; Joanne Spetz PhD, FAAN (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2018)
Health information technology (HIT) is increasingly adopted by nursing homes to improve safety, quality of care, and staff productivity. We examined processes of HIT implementation in nursing homes, impact on the nursing home workforce, and related evidence on quality of care. We conducted a literature review that yielded 46 research articles on nursing homes’ implementation of HIT. To provide additional contemporary context to our findings from the literature review, we also conducted semistructured interviews and small focus groups of nursing home staff (n = 15) in the United States. We found that nursing homes often do not employ a systematic process for HIT implementation, lack necessary technology support and infrastructure such as wireless connectivity, and underinvest in staff training, both for current and new hires. We found mixed evidence on whether HIT affects staff productivity and no evidence that HIT increases staff turnover. We found modest evidence that HIT may foster teamwork and communication. We found no evidence that the impact of HIT on staff or workflows improves quality of care or resident health outcomes. Without initial investment in implementation and training of their workforce, nursing homes are unlikely to realize potential HIT-related gains in productivity and quality of care. Policy makers should consider creating greater incentives for preparation, infrastructure, and training, with greater engagement of nursing home staff in design and implementation.